Compositional dependence of the optical properties on amorphous Agx(Ge0.25Se0.75)100 − x thin films - Conde Garrido, Juan Manuel (2013)
The effect of silver content on the optical properties of films of Agx(Ge0.25Se0.75)100 − x (with x ≤ 25 at.%) chalcogenide glasses has been analysed. The films were prepared by pulsed laser deposition from bulk glass target. Morphology, structure and optical properties of the films were characterized by profilometry, X-ray diffraction and UV–visible–NIR transmission spectroscopy (wavelength 400-2500 nm). Refractive index, absorption coefficient, and the optical band gap energy were determined. It was found that the refractive index increases (for every wavelength) whereas the optical band gap energy decreases as the silver content increases.